METHODOLOGY FOR IMPROVING THE PHYSICAL FITNESS OF STUDENT GIRLS THROUGH AEROBICS TOOLS - Mehrinigor Shavkatovna Yaxshiyeva (Research Focus International Scientific Journal, 2025)
The practical significance of the results of the study in this scientific research work is explained by the fact that higher education institutions are based on the results obtained on the basis of a questionnaire on the use of aerobics waxes during extracurricular activities, in order to increase the physical fitness of student girls, improve the levels of performing “physical fitness level” sports tests by age categories.